Unexpected efficiency boosting in CO2-microemulsions: a cyclohexane depletion zone near the fluorinated surfactants evidenced by a systematic SANS contrast variation study1. Issue 8 (28th February 2015) - Pütz, Y.; Grassberger, L.; Lindner, P.; Schweins, R.; Strey, R.; Sottmann, T.
<x xml:space="preserve">Abstract</x> Concentration gradient of cyclohexane in a CO2/cyclohexane swollen micelle stabilized by fluorinated surfactants revealed by the GIFT analysis of a SANS contrast variation.